Sustainable Development and Economic Growth: A Reality or an Oxymoron? - El Chami , Daniel (European Scientific Journal, ESJ, 2021)
The word "sustainable" is on everyone’s lips and every publication; however, it is over-and misused as a trend for marketing and profit purposes, sometimes unethically for "greenwashing". This distortion creates an obstacle in creating a more sustainable world and leads authors to describe sustainable development and economic growth as oxymorons. This paper describes the relationship between sustainable development and economic growth and explains how sustainability reporting, particularly management, governance and social disclosures (GRI 100), could effectively stimulate economic growth. However, to reach a sustainable model, the paper recommends a mental and theoretical transformation in economic growth’s perception to move from profit maximisation to optimisation. Finally, the manuscript calls to intensify research in this direction for a sustainable transformation of our society.